Hubungan Excessive Gestational Weight Gain Trimester III Dengan Kejadian Preeklamsia Pada Ibu Hamil - Dr. Febrianti, S.ST.,M.Keb; Indah Sri Wahyuni; Aulia Echi; Riska Amelia Putri (Politeknik Karya Husada, 2026)
Abstract Background: Preeclampsia is one of the pregnancy complications that contributes to maternal morbidity and mortality. Excessive gestational weight gain (EGWG) during pregnancy is suspected to play a role as a risk factor for the occurrence of preeclampsia. This study aims to analyze the relationship between third trimester EGWG and the incidence of preeclampsia in pregnant women. Methods: A quantitative study with a cross-sectional design was conducted on 40 pregnant women selected using a total sampling technique. Data were obtained from medical records and Maternal and Child Health (MCH) books, then analyzed using the Chi-Square test with a significance level of 5%. Results: A total of 18 respondents (45.0%) experienced third trimester EGWG and 19 respondents (47.5%) experienced preeclampsia. Bivariate analysis showed a significant relationship between third trimester EGWG and the occurrence of preeclampsia (p < 0.001). Conclusion: Excessive gestational weight gain in the third trimester is significantly associated with the occurrence of preeclampsia in pregnant women. Monitoring weight gain during pregnancy needs to be optimized as part of the early detection and prevention of preeclampsia in antenatal care. Integrated monitoring of weight gain in antenatal care services and strengthening education related to diet and healthy lifestyle need to be optimized to support the prevention of preeclampsia and improve maternal health. Keywords: Excessive gestational weight gain, pregnant mother, preeclampsia, third trimester.